Doses de Fósforo e seu efeito na cultivar de Mandioca IAC-14 no município de Gurupi-TO - Ribeiro, Laynne Lopes Guimarães (Universidade Federal do Tocantins, 2021)
Cassava in Brazil is grown mainly by small farmers, especially in soils with low fertility. Phosphorus is an essential element for the supply of energy for the metabolism of plants, and it is little studied in the culture of cassava. This work aimed to evaluate the behavior of the cultivar IAC-14 as a function of phosphorus doses, under the conditions of Gurupi-TO. The experiment was installed in a completely randomized block design, with four replications, with the treatments being doses of P2O5 (0, 50, 100, 150) kg ha-1, applied in the form of Simple Superphosphate) at planting. The characteristics evaluated were root length, stem diameter, root diameter, root number and total fresh root weight at 18 months after planting. Doses of phosphorus applied in the form of Simple Superphosphate significantly influenced the length and diameter of roots, the diameter of the stem and fresh weight of the roots of cultivar IAC-14 in soils of the cerrado. The characteristics of root diameter with an average of 68.65 mm at a dose of 100 kg ha-1 of P2O5, with a maximum efficiency point of 102.75 kg ha-1 of P2O5 results in a productivity of 65 kg ha-1. There was no significant effect of phosphate fertilization Simple Superphosphate on the number of roots and on the productivity of cassava roots cultivar IAC-14.